Investigation of Structural and Thermal Properties of Graphene Oxide Reinforced Epoxy Nanocomposites. (1st April 2022) - Gaur, M. S.; Raghav, Rajesh Kumar; Sagar, Rohan; Tiwari, R. K.
Abstract : The nanocomposites thin film was prepared by adding exfoliated GO in epoxy-hardner solution in different weight ratio. We investigate the thermal and surface properties of epoxy-graphene oxide (GO) nanocomposites using differential scanning calorimetry (DSC), fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM) and contact angle measurement method. AFM and contact angle results are supporting that graphene oxide provides the best reinforcement in epoxy. AFM is investigated the dispersion of GO and structural morphology of epoxy nanocomposites. The FTIR results show that exfoliated GO of two-dimensional (2D) shape favors the hardening process of the epoxy matrix, increasing its reaction rate by observing an epoxy stretching frequency at 907 cm −1 . The GO modified with amino group of epoxy lead to the increase of crosslinking density. FTIR absorption peak in 1700–1500 cm −1 regions is due to amino group. This attributes the significant increase of glass transition temperature of epoxy/GO nanocomposites . The contact angle and surface roughness increases with increase in concentration of GO in epoxy shows roughness induced hydrophobic surface. The solid surface energy was calculated by contact angle favors the good dispersion of GO in epoxy matrix.